Ondansetron use for children under 2-year old on postsurgical nurse controlled analgesia. Issue 5 (22nd April 2012) - Law, A; Lo, A; Christiansen, N
Abstract : Objective: Postoperative nausea and vomiting (PONV) is a common side effect of surgery. Risk factors include the use of opioids, type and length of surgery. One study suggests that postoperative vomiting occur in 13–42% of all paediatric surgery. 1 Nurse controlled analgesia (NCA) consists of a regular background infusion of morphine with intermittent boluses which can be given by nurses. Pro re nata (PRN) intravenous ondansetron is regularly prescribed for patients on NCAs as per trust guidelines. 2 Ondansetron is licensed in patients over 1 month for PONV 3 but from a literature review its use is limited in children under 2 year old as there is very little information on their effectiveness. The object of this audit is to find out current use and efficacy of ondansetron for PONV in patients under 2 year old with the aim to determine whether ondansetron is required to prevent potential polypharmacy issues, pharmaceutical interactions and side effects. Methods: Data were collected over a two month period on 20 patients from paediatric wards at The Royal London Hospital during January and February 2011. Patients were identified by the paediatric pain clinical nurse specialists (CNS) from the following inclusion criteria: ▶ Children <2 years; ▶ Child recently stopped postoperative NCA; ▶ Child without history of severe nausea or vomiting; ▶ Child not currently undergoing chemotherapy. Data collected included whether intravenous ondansetron was prescribed, whether the dose of 0.1 mg/kg was used, number of doses given, number of vomiting episodes, whether a nasogastric (NG) feeding tube was in situ and if it was regularly aspirated. Results: Nine patients (45%) had ondansetron prescribed, zero received any ondansetron, three (15%) had a recorded number of vomits, eight (40%) had a NG tube in place while on NCA, of which all eight were regularly aspirated. No patients required any ondansetron while on NCA. The three patients who vomited did so immediately after feeding and considered a fault of possetting rather than NCA or surgery related. Despite Trust guidelines only 45% of patients audited were prescribed ondansetron. All NG insertion and aspiration occurred on the high dependency neonatal surgical ward. Many of these patients return from theatre nil by mouth and the usual practice is to aspirate the NG tubes on an hourly basis until the doctor decides that the patient can slowly be re-introduced with feeds. The patients who vomited did so immediately after feeding and the size and severity was considered small and minor. Retrospective data collection for two patients who vomited showed they underwent gastroenterology surgery (closure of colostomy) and pyloplasty respectively. Conclusion: With no doses given it is recommended that ondansetron no longer be prescribed routinely for this patient group. This allows doctors to review the severity of vomiting and prevents unnecessary administration. Further data collection (higher patient numbers and type of surgery) is needed to consolidate the findings.